Offshore outsourcing to Russian IT providers: Opportunities, risks and best practice procedures - Stephan Weinert; Mathias Weber; David Vasak (University of Wuppertal, Schumpeter School of Business and Economics, 2008)
Outsourcing IT to specialized providers 'off-shore' has become an important option for many western companies for maintaining or improving their competitiveness. The vast majority of those specialized IT providers are located in Asia, especially in India. Relatively little is known though about Russian IT provider market. To provide IT decision makers with deeper insights, this article provides the necessary theoretical foundations as well as practical information about the Russian IT provider market based on extensive market research and project experiences.
urn:nbn:de:hbz:468-20080675
Keywords: 330; IT-Dienstleister; Auslandsverlagerung; IKT-Sektor; Lieferant; Markt; Russland